An ImageJ tool for simplified post-treatment of TEM phase contrast images (SPCI). (June 2019) - Amandine, Verguet; Cédric, Messaoudi; Sergio, Marco; Patricia, Donnadieu
Highlights: Simplified numerical post-treatment to retrieve phase-contrast from TEM images. ImageJ plugin suitable for phase retrieval from a very limited focal series. Numerical image treatment requiring a single adjustable parameter only. Abstract: Tools for taking advantage of phase-contrast in transmission electron microscopy are of great interest for both biological and material sciences studies as shown by the recent use of phase plates and the development of holography. Nevertheless, these tools most often require highly qualified experts and access to advanced equipment that can only be considered after preliminary investigations. Here we propose to address this issue by the development of an ImageJ plugin that allow the retrieval of a phase image by simple numerical treatment applied to two defocused images. This treatment based on Tikhonov regularization requires the adjustment of a single parameter. Moreover, it is possible to use this approach on one-image. Although in that case the retrieved image gives only qualitative information, it is able to enhance the image contrast appropriately. This can be of interest for specimens producing low contrast images under the electron microscopes, such as some frozen hydrated biological samples or those sensible to electron radiation unsuitable for holographic studies.